Molecular Investigation of Theileria and Babesia Species in Domestic Mammals from Sardinia, Italy - Valentina Chisu; Elisa Serra; Cipriano Foxi; Giovanna Chessa; Giovanna Masala (Veterinary Sciences, 2023)
Piroplasmoses are tick-borne diseases caused by hemoprotozoan parasites of veterinary and public health significance. This study focuses on the molecular identification and characterization of species belonging to the Theileria/Babesia genera in 152 blood samples, collected from 80 horses and 72 cattle from several farms in Sardinia, by targeting the 18S rRNA gene. The PCR results highlighted that 72% of the samples were positive for Theileria/Babesia spp., with a rate of infection of 68% and 75% for the horses and cattle, respectively. Sequencing and the BLASTn analysis showed that the 18S rRNA generated in this study has 99–100% homology with the B. bigemina, T. orientalis/sergenti/buffeli, T. equi and T. annulata strains isolated from different hosts worldwide. These findings improve the knowledge on Babesia and Theileria infections in domestic mammals and confirm the significant prevalence of piroplasmosis among subclinical and carrier animals throughout the island. Furthermore, the presence of T. annulata, reported for the first time in the study area, expands the repertoire of pathogens already detected in Sardinia. Our results gather updates on the diversity and distribution of piroplasms in Sardinia and suggest the need to develop procedures to improve animal and public health safety.